Exam Ref MS-100 Microsoft 365 identity and services - Thomas, Orin, 1973- (Microsoft Press : Pearson Education, 2020)
Prepare for Microsoft Exam MS-100 -and help demonstrate your real-world mastery of skills and knowledge needed to effectively design, deploy, manage, and secure Microsoft 365 services. Designed for experienced IT professionals, Exam Ref focuses on critical thinking and decision-making acumen needed for success at the Microsoft Certified Expert level. Focus on the expertise measured by these objectives: Design and implement Microsoft 365 services Manage user identity and roles Manage access and authentication Plan Office 365 workloads and applications This Microsoft Exam Ref: Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Assumes you have working knowledge of Microsoft 365 workloads, networking, server administration, and IT fundamentals; and have administered at least one Microsoft 365 workload About the Exam Exam MS-100 focuses on knowledge needed to manage domains; plan a Microsoft 365 implementation; set up and manage Microsoft 365 tenancy and subscriptions; plan user and data migration; design identity strategy; plan and manage identity synchronization with Azure AD Connect; manage Azure AD identities and user roles; manage authentication; implement MFA; configure application access; implement access for external users of Microsoft 365 workloads; and plan Office 365 workload and applications deployment. About Microsoft Certification Passing this exam and Exam MS-101 Microsoft 365 Mobility and Security (and earning one Microsoft 365 workload administrator certification or the MCSE Productivity certification) fulfills your requirements for the Microsoft 365 Certified Enterprise Administrator Expert certification credential. This demonstrates your ability to evaluate, plan, migrate, deploy, and manage Microsoft 365 services.